2014
DOI: 10.1186/1476-4598-13-210
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG promotes tumor cell survival from tumor necrosis factor-α-induced apoptosis

Abstract: BackgroundIncreased incidence of lung cancer among pulmonary tuberculosis patients suggests mycobacteria-induced tumorigenic response in the host. The alveolar epithelial cells, candidate cells that form lung adenocarcinoma, constitute a niche for mycobacterial replication and infection. We thus explored the possible mechanism of M. bovis Bacillus Calmette-Guérin (BCG)-assisted tumorigenicity in type II epithelial cells, human lung adenocarcinoma A549 and other cancer cells.MethodsCancer cell lines originating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…30 TNF-a is one of the inducers of apoptosis 31 and functions by suppressing p53. 32 The present data show that IL-13 also suppresses caspase 3 and TNF-a in the CD4…”
Section: Discussionsupporting
confidence: 55%
“…30 TNF-a is one of the inducers of apoptosis 31 and functions by suppressing p53. 32 The present data show that IL-13 also suppresses caspase 3 and TNF-a in the CD4…”
Section: Discussionsupporting
confidence: 55%
“…It has been previously reported that lung carcinogenesis can be induced by chronic TB infection in a mouse model 49 , and that BCG can promote the survival of A549 and several other tumor cells from TNFα-induced apoptosis thereby promoting tumorigenesis in xenograft studies 50 . Furthermore, Mtb-infected THP-1 cells can induce epithelial mesenchymal transition (EMT) in the lung adenocarcinoma epithelial cell line A549 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers enhance macrophage cytotoxicity through specificity to stimulate activation, such as by adding M-CSF and muramyl dipeptide (MDP) when macrophages are cultured in vitro to enhance macrophage cytotoxicity; by using the adoptive transfer treatment to achieve anti-tumor effects; or by using intravenous liposomes that load immune modulators to enhance the toxicity of macrophages. The molecules of microbial agents and pathogens can stimulate the antitumor cytotoxicity of macrophages, such as using bacilli calmette-guerin (BCG) in the treatment of bladder cancer, through stimulating macrophages to increase the cytotoxicity of macrophages to certain bladder cancer cell lines (55). In addition, there is evidence that the increased levels of IL-6, IL-12, and TNF in the urine of bladder cancer patients treated with BCG may be related to the enhancement of the function of macrophages.…”
Section: Enhancing the Toxicitymentioning
confidence: 99%